Illustrated Japanese characters 13 (Japan, 1997)
This book consists of the following four section: Japanese characters, Kanji and Jukugo, Everyday Kanji, and Kanji culture.
Keywords: Chinese characters,Chinese language,Japanese language; Japan,Etymology,Textbooks for foreign speakers; English